Peran Komunikasi Interpersonal dalam Rekonstruksi Identitas Pribadi dan Kolektif pada Komunitas Skena Surabaya Tahun 2025 - Sulung Rahmat Aji; Fatihatul Lailiyah; Moch. Ichdah Asyarin Hayau Lailin (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explore how interpersonal communication plays a role in the process of constructing self-identity within the “Jemuah Keos” community in Surabaya. This community functions as an alternative social space inhabited by individuals with diverse creative backgrounds, such as musicians, motorcycle builders, visual artists, and subculture enthusiasts. The formation of identity in this community is not solely driven by individual expression but also shaped through social interactions that are reflective and rich in meaningful symbols. The study uses a qualitative approach with a descriptive case study method. Data were collected through participatory observation, semi-structured interviews with nine informants, and documentation of various visual artifacts representing the community’s activities. The data analysis process follows the interactive model by Miles and Huberman, which consists of three main stages: data reduction, data presentation, and drawing conclusions. The theoretical framework used in this study refers to Joseph A. DeVito's concept of interpersonal communication, which includes self-disclosure, empathy, emotional support, symbolic exchange, social values, as well as reflective interaction and role negotiation in social relationships. The findings indicate that interpersonal communication is a key element in shaping and negotiating personal identity. Cultural symbols such as clothing style, vehicle modifications, visual language, and daily interaction patterns become primary means of identity expression. The